Kesiapan Pelaksanaan Pembelajaran Dari Rumah Ditengah Pandemi Covid-19 (IPF: Inovasi Pendidikan Fisika, 2021)
In suggestion with the government's recommendation as an impact of overcoming the COVID-19 virus, it is necessary to implement social restrictions, social restrictions on schools throughout the country in an effort to stop the spread of COVID-19 in this case social restrictions also have an impact on the world of education with the implementation of studying from home (Study from home) . Online learning (online) during this pandemic provides a new space for learning, because learning can still be done while obeying the government's appeal for social restrictions in the midst of this pandemic. This study uses a descriptive qualitative approach and method. The percentage of student responses to how well the teacher teach online learning materials is in a good category, this indicates that the teacher is ready to present online learning with all interesting learning media so that students can better understand that learning Keywords: education, Online Learning, Covid-19